Cognitive neuroscience: trickle-down theories of vision. - O'Shea, J; Walsh, V (2006)
The visual cortex is not a passive recipient of information: predictions about incoming stimuli are made based on experience, partial information and the consequences of inferences. A combination of imaging studies in the human brain has now led to the proposal that the orbitofrontal cortex is a key source of top-down predictions leading to object recognition.